2021
DOI: 10.1017/s0967199421000915
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between protein kinases A and C regulates sea urchin sperm motility

Abstract: Summary Fertilization, a crucial event for species preservation, in sea urchins, as in many other organisms, requires sperm motility regulation. In Strongylocentrotus purpuratus sea urchins, speract, a sperm chemoattractant component released to seawater from the outer egg layer, attracts sperm after binding to its receptor in the sperm flagellum. Previous experiments performed in demembranated sperm indicated that motility regulation in these cells involved protein phosphorylation mainly due to the cAMP-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…White et al [32] demonstrated the existence of a correlation between motility and the level of phospho-PKC substrates, so PKC activation and phosphorylation of its target proteins represent a significant requirement for the maintenance of motility in the spermatozoa of intact sea urchins. In S. purpuratus, the levels of PKC substrates contribute to the production of immotile and motile spermatozoa, and non-competitive PKC inhibitors are involved in diminishing the circular velocity of spermatozoa [36].…”
Section: Molecular Switches In Signal Transductionmentioning
confidence: 99%
“…White et al [32] demonstrated the existence of a correlation between motility and the level of phospho-PKC substrates, so PKC activation and phosphorylation of its target proteins represent a significant requirement for the maintenance of motility in the spermatozoa of intact sea urchins. In S. purpuratus, the levels of PKC substrates contribute to the production of immotile and motile spermatozoa, and non-competitive PKC inhibitors are involved in diminishing the circular velocity of spermatozoa [36].…”
Section: Molecular Switches In Signal Transductionmentioning
confidence: 99%